The geo-archaeological study at the galatara proto-historic burial site at kegalle, sri lanka - Ranaweera, D. (University of Jaffna, 2012)
The upper valleys of river basin should be studied for a better understanding of the early Iron Age cultural landscape and for the purpose of looking at alternative Iron Age sites in Wet Zone, Sri Lanka. This study investigates the environmental conditions of the proto-historic culture at Galatara, Kegalla, explains the relationship between to the location of this site, the environmental elements and investigates the cultural relationships with other archaeological sites which located at the upper Maha oya basin. Field work was performed to record the observations of the physical properties to support the data a comparative study or literary evidences was carried out. This is a solitary cist burial site located in the wet low-mountain area of Sri Lanka. The burials are found between the Urakanda range and the Bible rock within the limits of the Marahenawatta. The archaeological site at Galatara can be identified as cist burials site around the Early Iron age. This site is situated at the turmeric garden at present, and this cist burial site located in a small hill area. Nowadays we can see two burials on the surface and others are under the earth. Two caps stones on the surface can be measured. These investigations revealed pots and vessels containing bones, charcoal, iron, weapons, and metal ornaments. Non Brahmi symbols cannot be seen inside surface of these two capstones. It is clear that the uniform pattern can be observed even within the river valleys of Sri Lanka. The Galatara, proto historic site located at upper Maha Oya valley would be a location important place for socio-economic activities at that time. Further studies are expected to provide a complete understanding of the total cultural ecological background around the Galatara site during the proto historic period.